Membrane-Disruptive Effect of Human Milk: Inactivation of Enveloped Viruses - Isaacs, Charles E. (J Infect Dis, 1986)
Fresh human milk treated with antibody to secretory IgA had no effect on viral infectivity but became antiviral after 1 hr in the stomachs of suckling infants. Antiviral activity also appeared in fresh milk stored at 4 C for at least two days. The antiviral activity, which reduced titers of virus by as much as 10,000-fold, only affected enveloped viruses and was localized in the milk lipid fraction. Its appearance in stored milk was apparently due to fatty acids released by the activity of milk lipases, particularly lipoprotein lipase. Antiviral activity in the infants' stomach, however, most likely resulted from the activity of gastric and linguallipases on milk triglycerides and caused the release of antiviral fatty acids. Milk and stomach contents that were antiviral also lysed cultured cells by disruption of their plasma membrane. Cell lysis was also caused by purified linoleic acid, which is a normal constituent of human milk triglycerides.